Growing Mother's Language Literation in A Family Environment - Dinar Nur Inten; Dewi Mulyani; Khambali Khambali; Syifa Aghnia Zaenal; Aida Nur Khairunnisa (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2020)
Language is identical to culture, so culture will be sustainable if the community's language is firmly held and used in their daily lives. As one of the regional languages that have a major contribution to the Indonesian nation's progress, the Sundanese language is preserved correctly by using and teaching and exemplifying its use to this nation's future generations. This study aimed to determine the use of the Sundanese language and parents' methods in introducing the Sundanese language to children. This study used a survey method for parents who have early childhood with respondents as many as 545. This study proves that family, parents, and the surrounding environment have a considerable influence in planting literacy in the mother tongue, namely Sundanese for children. Through parents' ability to determine methods, packaging engaging activities, and designing innovative, creative media for learning Sundanese, it can help develop mother tongue literacy skills for children. It is proven that 45.9% of children can tell the Sundanese language, and 39.8% of children can speak Sundanese. and 51.4% of children are capable enough to use Sundanese in their daily life.Keywords: Mother Language, Literacy, Family, Sundanese Language. AbstrakBahasa identik dengan budaya, maka suatu budaya akan berkelanjutan apabila bahasa masyarakat tersebut dipegang teguh dan digunakan dalam kesehariannya. Bahasa Sunda sebagai salahsatu bahasa daerah yang memiliki sumbangsih besar untuk kemajuan bangsa Indonesia sudah sewajarnya dijaga kelestariannya, dengan tetap menggunakan dan mengajarkan serta mencontohkan penggunaannya kepada para generasi penerus bangsa ini.  Tujuan penelitian ini untuk mengetahui penggunaan bahasa sunda dan metode yang digunakan para orang tua dalam mengenalkan bahasa sunda pada anak. Penelitian ini menggunakan metode survey kepada para orang tua yang memiliki anak usia dini dengan responden sebanyak 545 orang. Hasil dari penelitian ini membuktikan bahwa keluarga, orang tua dan lingkungan sekitar memiliki pengaruh yang cukup besar dalam penanaman literasi bahasa ibu yaitu bahasa Sunda untuk anak. Melalui kemampuan orang tua dalam menentukan metode, mengemas kegiatan yang menarik serta mendesain media kreatif inovatif untuk pembelajaran bahasa Sunda dapat membantu mengembangkan kemampuan literasi bahasa ibu bagi anak hal ini terbukti 45,9% anak mampu bercerita bahasa Sunda dan 39,8% anak mampu ngawih dan 51,4% anak cukup mampu untuk menggunakan bahasa Sunda dalam kesehariannya. Kata Kunci: Bahasa Ibu, Literasi, Keluarga, Bahasa Sunda.